Bilateral renal angiomyolipoma not assocated with tuberous sclerosis: A case report - Khaled, A; Arif, NUM; Zaman, W; Nasir, TA (Pulse, 2011)
Angiomyolipoma is a tumour composed of varying admixtures of bloodvessels, smooth muscles and adipose tissue.Renal angiomyolipoma can be unilateral or bilateral. Bilateral angiomyolipoma has a very strong association with tuberous sclerosis. In non tuberous sclerosis patient, bilateral renal angiomyolipoma is relatively rare. We have described a 49 year old non tuberous sclerosis female presented with bilateral renal angiomyolipoma. Renal angiomyolipoma commonly behaved in a benign way and resection is curative in most of the cases. DOI: http://dx.doi.org/10.3329/pulse.v4i1.6965 Pulse Vol.4 January 2010 p.36-37